2013
DOI: 10.1007/s12094-013-1126-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of MTHFR C677T polymorphisms and colorectal cancer risk in Asians: evidence of 12,255 subjects

Abstract: This meta-analysis indicated that the MTHFR 677 TT homozygous genotype decreased the risk of CRC in Asians, while the MTHFR 677 CT heterozygous genotype did not contribute to CRC susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…ERCC1 is a critical protein in the nucleotide excision repair pathway that is responsible for repairing damaged DNA, functional genetic polymorphisms in the ERCC1 gene thus may alter DNA repair capacity and modulate cancer susceptibility [6]. The C8092A (rs3212986) and T19007C (rs11615) analyzed in the current study were the common SNPs in exons of ERCC2 gene.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…ERCC1 is a critical protein in the nucleotide excision repair pathway that is responsible for repairing damaged DNA, functional genetic polymorphisms in the ERCC1 gene thus may alter DNA repair capacity and modulate cancer susceptibility [6]. The C8092A (rs3212986) and T19007C (rs11615) analyzed in the current study were the common SNPs in exons of ERCC2 gene.…”
Section: Discussionmentioning
confidence: 92%
“…Although increasing evidence suggests that environmental factors and chemical carcinogens, such as tobacco use and heavy alcohol intake, are probable etiological factors contributing to HNSCC susceptibility, only a small fraction of people exposed to these carcinogens will develop HNSCC [2,3]. HNSCC development is widely recognized as a stepwise process with involvement of a series of genetic alterations [4], and single-nucleotide polymorphisms (SNPs) for the associations between genomic regions and cancers in candidate genes offer a superior strategy for unraveling genetic complexity [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This transformation may increase the plasma homocysteine (Hcy) concentration and decreases the plasma folic acid concentration [ 26 ]. Recently, several meta-analyses indicated that MTHFR rs1801133 G>A polymorphism decreased the risk of CRC in Asians [ 27 , 28 ]. MTHFR rs1801133 G>A polymorphism locates on the NH2-terminal catalytic domain.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of MTHFR C677T polymorphism on cancer risk were controversial. Recent published meta-analyses showed that 677 C > T variation might contribute to the development of breast and esophageal cancer 47 48 ; however, a decreased cancer risk was observed in colorectal cancer 49 . Thus, MTHFR C677T polymorphism may play various roles in different carcinomas.…”
Section: Discussionmentioning
confidence: 99%